Development of β-Carotene-Fortified Chocolate Bar Using Kansei Engineering Method - Sidik, Gusmon; Ushada, Mirwan; Ainuri, Makhmudun (Department of Agro-industrial Technology, University of Brawijaya, 2025)
Abstractβ-carotene fortified chocolate bars have the potential to bridge the need for enjoyment and health amidst the risk of diabetes and the demand for functional foods. This study developed an integrative approach to design a β-carotene fortified chocolate bar that balances emotional, technical, sensory, and economic aspects. The research objective was to produce a stable, preferred, and economical formulation through the integration of Kansei Engineering, Taguchi design, Grey Relational analysis, and cost linear programming. The Kansei process identified 4 main factors of perception, while the Taguchi design produced 9 concepts that were tested for their physicochemical properties, β-carotene content, and hedonic attributes. The results showed Concept 7 as the best technical candidate with 95.29 μg/g β-carotene retention, stable color, and dense texture. Preference analysis placed Concept 5 as the hedonic optimum with 91.10 μg/g β-carotene content and the highest level of preference. Consuming a 30 g β-carotene-fortified chocolate bar provides 2.73-2.85 mg of β-carotene, or approximately 62-71% of the daily requirement. Linear programming results indicate that both formulations meet the Indonesian National Standard quality limits with a minimum cost of approximately IDR158.84-163.79/g and reflect a consistent relationship between Kansei phrases and functional product design parameters.Keywords: β-carotene, chocolate bar, formulation optimization, Kansei engineering, linear programming AbstrakCokelat batang yang difortifikasi β-karoten berpotensi menjembatani kebutuhan kenikmatan dan kesehatan di tengah risiko diabetes dan tuntutan pangan fungsional. Penelitian ini mengembangkan pendekatan integratif untuk merancang cokelat batang yang difortifikasi β-karoten yang seimbang antara aspek emosional, teknis, sensoris, dan ekonomi. Tujuan penelitian adalah menghasilkan formulasi yang stabil, disukai, dan ekonomis melalui integrasi Kansei Engineering, rancangan Taguchi, analisis Grey Relational, dan pemrograman linear biaya. Proses Kansei mengidentifikasi 4 faktor utama persepsi, sedangkan rancangan Taguchi menghasilkan 9 konsep yang diuji secara fisikokimia, kandungan β-karoten, dan uji hedonik. Hasil menunjukkan Konsep 7 sebagai kandidat teknis terbaik dengan retensi β-karoten 95,29 μg/g, warna stabil, dan tekstur padat. Analisis preferensi menempatkan Konsep 5 sebagai optimum hedonik dengan kadar β-karoten 91,10 μg/g dan tingkat kesukaan tertinggi. Konsumsi 30 g cokelat batang yang difortifikasi β-karoten memberikan asupan β-karoten 2,73-2,85 mg atau sekitar 62-71% kebutuhan harian. Hasil pemrograman linear menunjukkan kedua formulasi memenuhi batas mutu Standar Nasional Indonesia dengan biaya minimum sekitar Rp158,84-163,79/g dan mencerminkan hubungan konsisten antara frasa Kansei dan parameter desain produk fungsional.Kata kunci: β-karoten, cokelat batang, Kansei engineering, optimasi formulasi, pemrograman linier